Environmental remediation of heavy metal ions by novel-nanomaterials: A review. (March 2019) - Wu, Yihan; Pang, Hongwei; Liu, Yue; Wang, Xiangxue; Yu, Shujun; Fu, Dong; Chen, Jianrong; Wang, Xiangke
Abstract: Recently, novel-nanomaterials with excellent sorption capacities, mild stability, and environmental-friendly performance, have enabled massive developments in capturing heavy metal ions. This review firstly introduces the preparation and modification of novel-nanomaterials (e.g., MOFs, nZVI, MXenes, and g-C3 N4 ). Then, the heavy metal ions' sorption properties and the impact of environmental conditions have been discussed. Subsequently, the sorption mechanisms are verified through batch experiments, spectral analysis, surface complexation models, and theoretical calculations. Finally, the applications prospects of novel-nanomaterials in removing heavy metal ion polluted water have also been discussed, which provide perspective for future in-depth research and practical applications. Graphical abstract: Image 1 Highlights: Novel-nanomaterials have shown excellent sorption capacity for toxic heavy metal ions and can reach the equilibrium quickly. The effect of environmental conditions on sorption behavior of novel-nanomaterials has been discussed, providing reference for practical application. The reaction mechanisms mainly include adsorption, reduction, and oxidation. The cost, toxicity, large-scale applications of novel-nanomaterials in commercial production are analyzed and the solutions are given. Abstract : The preparation and surface modification of novel nanomaterials and their application in environmental pollution were overviewed. The sorption mechanism was discussed from spectroscopy analysis, surface complexation and theoretical calculations.